ISLAM DAN ETIKA LINGKUNGAN DALAM PRAKTIK MUSLIM DI INDONESIA: DARI TEKS KEAGAMAAN KE AKSI SOSIAL-RELIGIUS - Muhammad Azis Muntaha; Sahri Ramadon (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study aims to analyze the involvement of Islamic mass organizations in mining management in Indonesia from the perspective of Islamic environmental ethics and to identify the ethical dilemmas arising from such involvement. This research employs a qualitative approach using a library research design combined with normative-critical analysis. Data were collected from academic sources, including journal articles, books, and policy documents, and analyzed using thematic analysis to identify key issues related to Islamic environmental ethics, extractivism, and the institutional roles of Islamic organizations. The findings reveal that Islamic environmental ethics is grounded in strong normative principles, such as khalifah (stewardship), amanah (trust), mizan (balance), and the prohibition of fasād (destruction). However, these values are not consistently implemented in institutional practices when confronted with extractive economic logic. The involvement of Islamic organizations in the mining sector generates ethical dilemmas characterized by tensions between religious mandates and economic interests, as well as the risks of moral co-optation and symbolic legitimation. These findings highlight the importance of positioning Islamic environmental ethics as a critical framework for evaluating economic practices and public policies affecting ecological sustainability.